Two Unpublished 19th Century Ethiopian Letters: From Emperor Tewodros to Sir Robert Napier, and from Däǧǧazmač Nǝguśe to Naib Hasän Bey - Pankhurst, Richard (Aethiopica, 2008)
The two letters here published supplement those in Sven Rubenson’s invaluable compilation “Tewodros and his Contemporaries”. The first letter throws intriguing light on Emperor Tewodros’s remarkably amical attitude to the British in the run-up to his military confrontation with them at Mäqdäla. The second letter, the background to which has still to be established, may be regarded as a contribution to our knowledge of däǧǧazmač Nǝguśe’s rule in Tǝgray.